Current trends in the development of pedagogical systems of ukraine in the conditions of digitalization of society - Olha Potapchuk (Kazimierz Wielki University, 2023)
The purpose of the work is to analyse the current trends in the development of domestic pedagogical systems in the context of digitalization of society. The research methodology consists in the use of methods of scientific analysis, pedagogical positions on the issues of digitalization of education, implementation of systemic and integrative approaches. The scientific novelty consists in highlighting the main trends of the prospective pedagogical system. The main trends include: humanization and humanitarianization; national orientation; openness; science; continuity; digitalization. An analysis of each trend is presented and their role in the development of education is determined. It has been established that the digitalization of education creates prerequisites for the wide implementation of psychological and pedagogical developments in pedagogical practice, which allow to intensify the educational process, implement learning ideas, including within the framework of new models. Conclusions. Summarizing the analysis of the main trends and features of pedagogical systems at the current stage, it is very important to take into account the orientation of global educational processes. This is primarily an orientation to the individual, development of creative potential; openness of education as a condition of professional flexibility, mobility of a specialist, his ability to self-education and professional self-development; the need for interconnection and coordination of various stages of professional training, retraining and advanced training. Therefore, in order to modernize the pedagogical system of Ukraine, the national traditions and prospects of the country should be determined, taking into account the current trends in the development of digital technologies and the experience of foreign education systems.